NPD TYPE C — WAY TO THE EFFECTIVE THERAPY THROUGH TIMELY DIAGNOSIS - L.S. Namazova-Baranova; L.S. Vysotskaya; A.M. Mamed"yarov; T.V. Margieva; N.D. Vashakmadze; A.K. Gevorkyan (Педиатрическая фармакология)
In recent years in expanding diagnostic capabilities and improved knowledge level diseases that were previously considered rare become increasingly identified. Along with the achievements of the pharmaceutical industry, timely diagnosis and adequate therapy appointment can often save the life of the child and delay the progression of the disease. This article focuses on a rare, genetically determined, pathology of lysosomal diseases group, inherited autosomal recessively — NPD type C. Different versions of the clinical course and diagnostic methods are showed in details. Take account of the existing in our country hypo diagnostics of this disease, the authors propose to put into practice a diagnostic algorithm «index of suspicion of the disease NP-C» in order to improve detection and timely initiation of pathogenetic therapy. Key words: rare diseases, storage diseases, lysosomal diseases, Niemann-Pick disease type C, diagnostics, clinical course, treatment, children. (Pediatric pharmacology. — 2011; 8 (6): 114–118).